Capillary Refill Time and Serum Lactate as Predictors of Mortality and Postoperative Extracorporeal Membrane Oxygenation Requirement in Congenital Heart Surgery - Gustavo Cruz; Santiago Pedroza Gómez; Akemi Arango; Paula A. Guevara; Carlos González; Jesus Aguirre; Andrea Valencia-Orozco; Antonio J. Suguimoto (MDPI AG, 2023)
Multiple tissue perfusion markers are described to guide therapy in critically ill pediatric patients undergoing congenital heart surgery. Given the advantages of capillary refill time, our goal is to determine its predictive capacity for mortality and postoperative extracorporeal oxygenation requirements in congenital heart surgery and compare it to serum lactate. We conducted a prospective cohort observational study in a single high-complexity university hospital. Serum lactate and capillary refill time were measured at five predetermined time points: preoperative, immediate postoperative, 6, 12, and 24 h after the surgery. Prolonged immediate postoperative, 6 h, and 12 h capillary refill time measurements turned out to be independent risk factors for both outcomes. The capillary refill time area under the curve ranged between 0.70 and 0.80, while the serum lactate resulted between 0.79 and 0.92 for both outcomes. Both tissue perfusion markers resulted in mortality and extracorporeal oxygenation requirement predictors. Given the advantages of capillary refill time over serum lactate, a monitoring strategy including these two perfusion markers should be considered for congenital heart surgeries.